Pakistan : First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Pakistan's First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. Pakistan's program is on track and has started to bear fruit. However, risks remain elevated. Strong ownership and steadfast reform implementation are critical to entrench macroeconomic stability and support robust and balanced growth. The authorities are committed to sustaining the progress on fiscal adjustment to place debt on a downward path. The planned reforms include strengthening tax revenue mobilization, including the elimination of tax exemptions and loopholes, and prudent expenditure policies. Preparations for a comprehensive tax policy reform should start early to ensure timely implementation. The authorities have adopted a comprehensive plan to address the accumulation of arrears in the power sector. Its full implementation is key to improve collection, reduce losses, and enhance governance. Timely and regular adjustment of energy tariffs will bring the sector in line with cost recovery.